2018
DOI: 10.1038/s41598-018-23962-7
|View full text |Cite
|
Sign up to set email alerts
|

Poultry hatcheries as potential reservoirs for antimicrobial-resistant Escherichia coli: A risk to public health and food safety

Abstract: Hatcheries have the power to spread antimicrobial resistant (AMR) pathogens through the poultry value chain because of their central position in the poultry production chain. Currently, no information is available about the presence of AMR Escherichia coli strains and the antibiotic resistance genes (ARGs) they harbor within hatchezries. Therefore, this study aimed to investigate the possible involvement of hatcheries in harboring hemolytic AMR E. coli. Serotyping of the 65 isolated hemolytic E. coli revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 45 publications
4
77
2
Order By: Relevance
“…NA resistance was most common, along with TE, AM, C, SXT, and CIP, while most of the strains were sensitive to CZ, AMC, CRO, and FOX. Similar findings of common resistance to NA, TE, AM, SXT, and CIP among E. coli isolates from avian origin and other food animals have been reported by many researchers from China (44), Egypt (45), France (46), Bangladesh (47), and Japan (19). Although phylogroups D and B2 were related to higher drug resistance patterns in previous reports (48), we did not find any B2 strains in poultry.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…NA resistance was most common, along with TE, AM, C, SXT, and CIP, while most of the strains were sensitive to CZ, AMC, CRO, and FOX. Similar findings of common resistance to NA, TE, AM, SXT, and CIP among E. coli isolates from avian origin and other food animals have been reported by many researchers from China (44), Egypt (45), France (46), Bangladesh (47), and Japan (19). Although phylogroups D and B2 were related to higher drug resistance patterns in previous reports (48), we did not find any B2 strains in poultry.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, the genes of virulence group I (lpfA, lpfAR141, lpfA0113, ureD, nleE, and efa1), which have a significant association with diarrhea (10), were negatively correlated with or unrelated to antibiotic resistance. There was no negative correlation among the antibiotics in aEPEC in this study, although we performed the analysis according to the method of Osman et al (45), who found a negative correlation between gentamicin and amoxicillin in Bacillus spp. in Egypt (45).…”
Section: Discussioncontrasting
confidence: 51%
“…A collection of pathogenic E. coli isolated from colibacillosis cases in Italy between 2008 and 2010 (when third‐generation cephalosporins were still used prophylactically in day‐old chicks) showed diverse ESBL or AmpC‐bearing plasmids on a background of multiresistance, in 8% of isolates (Niero et al., ), consistent with multiple introductions or selection events. A similar but far more marked picture of extended‐spectrum cephalosporin resistance plus multiple other resistances was seen in E. coli isolates from Egyptian hatcheries (Osman et al., ).…”
Section: Transmission and Persistence Of Antimicrobial‐resistant Orgamentioning
confidence: 60%
“…A collection of pathogenic E. coli isolated from colibacillosis cases in Italy between 2008 and 2010 (when third-generation cephalosporins were still used prophylactically in day-old chicks) showed diverse ESBL or AmpC-bearing plasmids on a background of multiresistance, in 8% of isolates (Niero et al, 2018), consistent with multiple introductions or selection events. A similar but far more marked picture of extended-spectrum cephalosporin resistance plus multiple other resistances was seen in E. coli isolates from Egyptian hatcheries (Osman et al, 2018). A study of enteric gram-negative bacteria (mostly E. coli) shed by suckler calves in the United States revealed that over 90% of calves were colonized by ESBL-expressing organisms in their first year, despite no use of subtherapeutic antimicrobials in the herd and no prior use of therapeutic antimicrobials in the calves (Mir et al, 2018).…”
Section: Intervention Study On Antimicrobial Usementioning
confidence: 82%
See 1 more Smart Citation